REGULATION AND LEGAL PROTECTION OF SEXTORTION AS ELECTRONIC-BASED SEXUAL VIOLENCE IN INDONESIA - Fikri Triandhika; Lies Sulistiani (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2025)
Electronic-based sexual violence in Indonesia has increased compared in prior years, one of which is sextortion. Practice of handling sextortion cases in Indonesia show that law enforcement institution only focus on the dissemination of victim sexual content, without following up with extortion and threats to perpetrators, also the absence of victims protection. Victims comply with the wishes of perpetrators and not brave enough to report because victims are worried that victim sexual content will be disseminated. Normative legal research is a research method are used by analyzing literature research, statutory research, and case study. The research results show that Article 14 Law Number 12 of 2022 on Sexual Violence Criminal Act can be used in handling sextortion cases because it has a more accommodating formulation and form of punishment, also provides comprehensive protection of victims.